The Effect of Buerger Allen Exercises on Diabetes Mellitus Patients’ Foot Sensitivity of Mantang Health Center Working Area in 2021 - Mumpuni Mumpuni; Dewi Purnamawati; Moh. Arip; Masadah Masadah; Citra Lorenza (Ridwan Institute, 2022)
Diabetes mellitus is a chronic metabolic disease that requires medical care and independent management education for the use of complications. Diabetes mellitus complications often occur. One is the sensitivity of the leg. Physical training is essential to keep the vascularity, strengthen the leg muscles, and prevent complications sensitivity feet. This study aims to acknowledge the effect of Buerger Allen exercise on the sensitivity of the feet of patients with diabetes mellitus in the Mantang Health Centre work area in 2021. This research used a pre- experimental design method with the form of one group pretest-posttest. The sample in the study amounted to 19 respondents, with the sampling technique being purposive sampling. The research instrument used a monofilament of 10 g to measure foot sensitivity. Data analysis was processed using the Wilcoxon test. Based on the results of the study, it was shown that the average sensitivity values of the feet on the right and left legs before the Buerger Allen exercise were 6.63 and 6.58. In contrast, the average value of the sensitivity of the feet on the right and left feet after the Buerger Allen exercise had increased as much as the respectively. 9.47 and 9.63. The results showed the effect of the Buerger Allen exercise on foot sensitivity (p-value = 0.000). Thus, Buerger Allen's exercise affects the sensitivity of the feet of patients with diabetes mellitus in the Mantang Health Centre working area in 2021.